Prevalence of Depression in Patients with Rheumatoid Arthritis attending Rheumatology clinic of Benghazi Medical Center - Boshalla, Neama; Aljafi, Najla; Albraky, Fathi; Roaeid, Ragab (Benghazi University Medical Journal, 2024)
Introduction: Depression is a common co-morbidity in Rheumatoid Arthritis (RA) patients, potentially affecting the severity of the disease. Aim: The study aims to assess the prevalence of depression in Libyan patients with RA and to evaluate their depressive symptoms and depression scores. Methods: This is a cross-sectional study conducted at the Rheumatology Clinic of Benghazi Medical Center. It includes RA patients attending the clinic over six months, using the Patient Health Questionnaire (PHQ-9) to assess depressive symptoms. Results: The study analyzed 157 patients, aged 17 to 71 (mean age 42.9 years), predominantly female (female to male ratio of 12.1:1). Most patients had secondary or university education 74 patients (47.1%). Over half had no co-morbidities, and 87.3% were receiving RA treatment. A family history of RA was noted in 32.5% of patients. Depression scores revealed: Minimal depression in 12.7% (no treatment needed), Mild depression in 20.4% (treatment based on clinical judgment), Moderate depression in 29.3% (treatment based on clinical judgment). Moderately severe depression in 19.7% (treatment with antidepressants or therapy). Severe depression in 17.8% (treatment with antidepressants with or without therapy). The mean depression score was 12.3, with no significant associations found with age, sex, residence, disease duration, family history, or Body Mass Index (BMI). Conclusion: In conclusion, RA patients exhibit a high prevalence of depression, which significantly impacts their quality of life and disease outcomes. The presence of co-morbidities further complicates management. Addressing the mental health of RA patients should be an integral part of their overall care plan.